A Conservative Approach to a Peripheral Ameloblastoma. (20th October 2016) - Borrello, Rocco; Bettio, Elia; Bacci, Christian; Valente, Marialuisa; Sivolella, Stefano; Mazzoleni, Sergio; Berengo, Mario
Abstract : Peripheral Ameloblastoma (PA) is the rarest variant of ameloblastoma. It differs from the other subtypes of ameloblastoma in its localization: it arises in the soft tissues of the oral cavity coating the tooth bearing bones. Generally, it manifests nonaggressive behavior and it can be treated with complete removal by local conservative excision. In this study we report a case of PA of the maxilla in a 78-year-old female patient and we describe the four different histopathological patterns revealed by histological examination. After local excision and diagnosis, we planned a long term follow-up: in one year no recurrence had been reported. The choice of treatment is illustrated in Discussion.